Institutional change and economic development / edited by Ha-Joon Chang - "Chang, Ha-Joon.(ed.)" (London, 2007)
The issue of institutional development has come to prominence during the last decade or so. During this period even the IMF and the World Bank, which used to treat institutions as mere details, have come to emphasise the role of institutions in economic development. However, there are still some important gaps that need to be filled before we can say that we have a good grip on the issue of institutions and economic development, both theoretically and at the policy level. This book is an attempt to fill these gaps. Recognizing the complexity of the issues involved, this book draws together contributions from scholars in economics, history, political science, sociology, public administration and business administration. These experts discuss not only theoretical issues but also a diverse range of real-life institutions political, bureaucratic, fiscal, financial, corporate, legal, social and industrial in the context of dozens of countries across time and space from Britain, Switzerland and the USA to today?'s Botswana, Brazil and China. The contributors show that there is no simple formula for institutional development. Instead, real-life examples of institutional development which has been achieved through a mixture of deliberate imitation of foreign institutions and local institutional innovations are discussed and studied. While arguing there is no set formula for institutional development, this book will assist developing countries to improve their institutions by providing sophisticated theoretical discussions and helpful policy ideas based on real-life cases.
Keywords: Economic development-congresses